Non-judicial dispute settlement in international financial transactions - Non-judicial dispute settlement in international financial transactions (International conference) (1999 Mar); Horn, Norbert; Norton, Joseph Jude. (London ; Boston : Kluwer Law International, 2000)
Aims to fill this gap in the literature of arbitration and non-judicial dispute settlement mechanisms and includes analyses of bank remedies, direct negotiation and mediation in financial and business conflicts, debt renegotiations, restructuring of syndicated loans, arbitration in project financing, and the roles of the ICC, NAFTA and OAS. Some of the expert papers focus in particular on the role of arbitration and dispute resolution in Latin America, Greater China and Russia.
Revised papers. Conference is part of a global series of conferences in 1999 on the "New international financial architecture".
Includes bibliographical references and index.
oif 02/03/15
Loan
Keywords: Banking law; Arbitration and award; Dispute resolution (Law); International financial transactions; Non-judicial dispute settlement; New international financial architecture